2013
DOI: 10.1021/np300900a
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Homoisoflavonoids and Bufatrienolides from Urginea depressa

Abstract: Investigation of the South African plant Urginea depressa Baker (Asparagaceae Juss.) for antiproliferative activity against the A2780 ovarian cancer cell line led to the isolation of the six new homoisoflavonoids urgineanins A-F (1 - 6), the two known bufatrienolides 7 and 9, and the new bufatrienolides urginins B and C (8 and 10). Structures were elucidated based on analysis of their 1D and 2D NMR spectra, electronic circular dichroism, and mass spectrometric data. Five of the six new homoisoflavonoids had go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 34 publications
3
32
0
Order By: Relevance
“…D. depressa has long been known to be toxic to sheep and cattle (Kellerman et al, 2005;Pooley, 2003;Van Wyk et al, 2002), but it is reported in the current study to cure diseases such as cancer, liver problems, HIV and mental illness. Recent studies have confirmed that five homoisoflavonoids urgineanins A-E (1-5), isolated from D. depressa showed strong antiproliferative activity against the A2780 ovarian cancer cell line (Dai et al, 2013). Similarly, P. heptandra is reported in the current study to cure cancer.…”
Section: Medicinal Plants Usedsupporting
confidence: 80%
“…D. depressa has long been known to be toxic to sheep and cattle (Kellerman et al, 2005;Pooley, 2003;Van Wyk et al, 2002), but it is reported in the current study to cure diseases such as cancer, liver problems, HIV and mental illness. Recent studies have confirmed that five homoisoflavonoids urgineanins A-E (1-5), isolated from D. depressa showed strong antiproliferative activity against the A2780 ovarian cancer cell line (Dai et al, 2013). Similarly, P. heptandra is reported in the current study to cure cancer.…”
Section: Medicinal Plants Usedsupporting
confidence: 80%
“…homoisoflavonoid (Yan et al, 2012;Dai et al, 2013). It also showed a singlet of two protons at d 5.91 ppm suggesting a methylenedioxyl moiety (Teponno et al, 2013b) and a singlet of three protons at d 3.81.…”
Section: Resultsmentioning
confidence: 98%
“…The unusual 3S-configuration has been reported once from the Urginiodeae subfamily, from Urginea depressa. 25 The isolation of compound 3 was facilitated by acetylation yielding two products, the 3'-acetate, (3A) and the 5,7-diacetate, (4) has been isolated previously from Urginea altissima, 26 Helleborus orientalis, and H. thibetanus (Ranunuclaceae). 27,28 Gamabufotalin-3-O-α-L-rhamnoside (5) has been isolated previously from Urginea altissima.…”
mentioning
confidence: 99%